STUDI PEMETAAN PEMBENTUKAN RUANG KOMUNAL PADA LAPANGAN LUMINTANG, DENPASAR-BALI - MADE ANGGITA WAHYUDI LINGGASANI; NI KOMANG INDRA MAHAYANI (GANEC SWARA, 2023)
The field of architecture has experienced spectacular developments over the years. This is because in the Public open space is a concept of space to accommodate people from all walks of life and backgrounds, in the sense that public open space must also consider the existence of people with disabilities. Community activity is one of the factors that can affect the utilization and sustainability of green open space. High community activity in green open space can increase community participation in the management and maintenance of green open space, so that green open space can be healthier and sustainable. However, uncontrolled community activities can cause damage to green open space, so it needs good management so that community activities can be directed, especially in the formation of communal spaces. The purpose of this study is to formulate community preferences in terms of community involvement in the green open space area in Denpasar, to formulate the factors that influence the formation of communal spaces in public open spaces in Denpasar City, as well as to study and visualize the mapping of communal spaces that occur in green open spaces. in Denpasar. The steps taken to realize this research are Determining Community Preferences in Communities to find out the preferences of the community as a community in choosing activities to use public open spaces in Denpasar City. Then proceed with the identification of the factors that influence the formation of communal space, followed by the identification of Behavioral Setting and Behavioral Mapping to conduct a study of the behavioral setting and mapping that occur as a result of community activities and public space to produce a mapping of communal space in public space as a visualization of patterns and forms of communal spaces that occur in public spaces in the city of Denpasar.